Effect of furosemide in the treatment of high-altitude pulmonary edema - Dava Tenzing; Pianduo Suolang; Deji Gesang; Duoji Suolang; Gaozhan Duan; Wangmu Ciren; Yihui Wang; Tongtian Ni (BMC Pulmonary Medicine, 2024)
Abstract Background High-altitude pulmonary edema (HAPE) refers to the onset of breathlessness, cough, and fever at rest after arriving at high altitudes. It is a life-threatening illness caused by rapid ascent to high altitudes. Furosemide is controversial in HAPE treatment but is routinely used in China. Further research is needed to assess its efficacy and impact on HAPE management and prognosis. The aim of this study is to determine the effectiveness of furosemide for HAPE. Methods A retrospective was conducted to analysis of patients with HAPE admitted to the People’s Hospital of Shigatse City from January 2018 to September 2023. Patients were divided into furosemide group and non-furosemide group for further analysis. Clinical variables including demographic information, comorbidities, vital signs, inflammatory markers, biochemical analysis, CT severity score and prognostic indicators were collected. Results A total of 273 patients were enrolled, with 209 patients in the furosemide group and 64 patients in the non-furosemide group. The furosemide group showed a significantly decrease in CT severity scores compared to the non-furosemide group. Subgroup analysis showed that the longer the duration of furosemide use, the more pronounced the improvement in lung CT severity scores. But there were no significant differences in length of hospital stay and in-hospital mortality between the two groups. Conclusion Furosemide helps alleviate pulmonary edema in HAPE patients, but further research is needed to clarify its impact on prognosis.